Alternatif Strategi Penanganan Dampak Ekonomi Covid-19 Pemerintah Daerah Jawa Timur Pada Kawasan Agropolitan - Ulya, Husna Ni’matul (El-Barka, 2020)
Abstract: The COVID-19 pandemic had a significant impact on the order of life of the world community, including in Indonesia. Besides health impacts, the pandemic also has economic impacts, so that it encourages the government to make various policies to overcome these impacts, including by forming task forces both at the central and regional levels. Policy by optimizing state and regional budgets for the needs of preventing the spread and handling of COVID-19 health impacts and optimizing the potential of the local economy for meeting the needs of the community in a sustainable manner. East Java is a superior area in agriculture which includes animal husbandry, fisheries, plantations, and forestry. One of the programs implemented is the development of agropolitan areas which are agricultural-based economic development in agribusiness areas, designed and implemented by synergizing the various potentials that exist to encourage the development of competitive, populist-based, sustainable and decentralized agribusiness business systems. and facilitated by the government. This study uses a literature study approach with the aim of exploring alternative East Java government policies in order to address the economic impact of COVID-19 by maximizing the agropolitan area. The results of the research resulted in the formulation by maximizing the development of the agropolitan area by strengthening regulations and expanding the agropolitan area to other regions / cities, and utilizing online media in the implementation including the marketing system of products from this agropolitan area even though it was in a pandemic.Abstrak: Pandemi COVID-19 memberikan dampak yang signifikan terhadap tatanan kehidupan masyarakat dunia termasuk di Indonesia. Selaian dampak kesehatan, pandemi juga memberikan dampak ekonomi, sehingga medorong pemerintah untuk membuat berbagai kebijakan untuk menanggulangi dampak tersebut, diantaranya adalah dengan membentuk satuan tugas baik di pusat maupun daerah. Kebijakan dengan mengoptimalkan anggaran negara dan daerah untuk kebutuhan pencegahan penyebaran dan penanganan dampak kesehatan COVID-19 dan optimalisasi potensi ekonomi lokal untuk pemenuhan kebutuhan masyarakat secara berkelanjutan. Jawa timur merupakan daerah yang unggul di bidang pertanian yang meliputi peternakan, perikanan, perkebunan, dan kehutanan. Salah satu program yang dijalankan adalah pengembangan kawasan agropolitan yang merupakan pembangunan ekonomi berbasis pertanian di kawasan agribisnis, dirancang dan dilaksanakan dengan cara mensinergikan berbagai potensi yang ada untuk mendorong berkembangnya sistem usaha agribisnis yang berdaya saing, berbasis kerakyatan, berkelanjutan dan terdesentralisasi, serta digerakan oleh masyarakat dan difasilitasi pemerintah. Penelitian ini menggunakan pendekatan studi literatur dengan tujuan untuk menggali alternatif kebijakan pemerintah Jawa Timur dalam rangka menangani dampak ekonomi COVID-19 dengan memaksimalkan kawasan agropolitan. Hasil Penelitian menghasilkan fomulasi dengan memaksimalkan pengembangan kawasan agropolitan dengan penguatan regulasi serta perluasan kawasan agropolitan ke wilayah/kota lain, dan memanfaatkan media online di dalam pelaksanaan termasuk sistem pemasaran produk dari kawasan agropolitan ini meskipun sedang dalam masa pandemi.